Translation Quality of Level Shift for English Noun Phrase into Indonesian. - Haryanti, Dwi (Prosiding University Research Colloquium, 2021)
The aim of this article is describing the translation quality of English noun phrases translated into Indonesian. The data of this descriptive qualitative study are phrases, clauses, and sentences containing of noun phrases found in English scientific and fiction texts translated into Indonesian. The data were analyzed by applying translation theories proposed by Nababan (2012) and Lauscher (2000). Based on the analyzed data, there are three elements of translation quality show accurate, acceptable, and readable. All variation of English noun phrase patterns translated into Indonsian have same meaning to the message of the source language. They are acceptable and easy to understand without reading the entire translation more than one. Therefore, the translation of noun phrases are readable for ideal readers of the translated texts. The result of this study can be applied in teaching learning process of translation subject, theory, practice, and evaluation in translation.